2018
DOI: 10.1007/s00497-018-0335-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of reactive oxygen species in pollen germination in Picea pungens (blue spruce)

Abstract: Endogenous ROS, including those produced by NADPH oxidase, are required for spruce pollen germination and regulate membrane potential in pollen tubes; [Formula: see text] and H O are unevenly distributed along the tube. Recently, the key role of reactive oxygen species (ROS) in plant reproduction has been decisively demonstrated for angiosperms. This paper is dedicated to the involvement of ROS in pollen germination of gymnosperms, which remained largely unknown. We found that ROS are secreted from pollen grai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 27 publications
4
50
0
Order By: Relevance
“…Thus, this ROS can be regarded as a normal component of the environment for pollen on stigma, which induces germination in angiosperms. Interestingly, for gymnosperms this pattern is not characteristic (Maksimov et al 2018).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Thus, this ROS can be regarded as a normal component of the environment for pollen on stigma, which induces germination in angiosperms. Interestingly, for gymnosperms this pattern is not characteristic (Maksimov et al 2018).…”
Section: Discussionmentioning
confidence: 96%
“…Hypothesis (2) has convincing evidence obtained using simplified in vitro model system (Potocký et al 2007;Smirnova et al 2009a): ROS quenching with Mn-TMPP (100-300 µM) significantly lowers the growth rate (Potocký et al 2007). Adding moderate concentrations of Mn-TMPP (H 2 O 2 and O 2 -• quencher) as well as DPI suppressed pollen germination both in tobacco and spruce (Smirnova et al 2009a;Maksimov et al 2018). On the other hand, the addition of exogenous ROS in moderate concentrations (100 µM for tobacco) activates germination (Smirnova et al 2009a); Despite this rather convincing data, detailed studies and comparison of pollen grain physiology in the presence of both ROS and the stigma exudate were needed to clarify the function of ROS on the receptive stigma surface.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…The distribution of inorganic ions is also strictly subjected to the principle of zoning, including gradient distribution of ionic currents through the plasma membrane as well as free inorganic ions in the cytoplasm (Michard et al 2017;Feijó and Wudick 2018;Zheng et al 2019). The latter is maintained due to the uneven allocation of ion transport systems and their activitywhich also results in the gradient distribution of membrane potential values, which has been to date revealed in 3 species, including lily (Breygina et al 2010;Maksimov et al 2018;Podolyan et al 2019).…”
Section: Introductionmentioning
confidence: 98%
“…Model experiments on protoplasts with exogenous ROS highlighted several aspects of pollen physiology related to redox-signaling, the main of which is ion homeostasis, as ion transport across the membrane is regulated by Н 2 О 2 Maksimov et al 2016). As Н 2 О 2 is the most stable ROS, all studies in vitro were confined to Н 2 О 2 , which was shown to have multiple effects in pollen tubes, both angiosperm (Podolyan et al 2019) and gymnosperm (Maksimov et al 2018). Studies on somatic plant cells that have been exposed to stress lead to the opinion that Н 2 О 2 doesn't affect "targets" that had been attributed to this ROS but rather binds to transition metal binding sites converting it to OH • (Demidchik 2015).…”
Section: Introductionmentioning
confidence: 99%